Evaluación y clasificación del alojamiento turístico para la satisfacción del cliente: caso Puerto López - Cedeño Moreira, José Armando (2022)
The objective of the research was to carry out the evaluation and classification of tourist accommodation as a contribution to improving customer satisfaction in the Puerto López destination. The type of research used was mixed with a descriptive approach, resulting in the methodology to be implemented. As a first phase, the diagnosis of the canton's accommodation service was carried out, where 67 establishments were identified, divided into hostels, hotels, hostels, residential hostels, inns, cabins, pensions and guest houses with a capacity for 2,324 people. The study focused on 4 hotels due to confinement due to the COVID-19 pandemic. The second phase addressed the evaluation and classification of accommodation establishments using the Accommodation Regulation Application Manual, resulting in the Berlin International hotel, the Nautilus, the Ancora and the Víctor Hugo hotel falling within the two-star category. And in the last stage, the evaluation of customer satisfaction was carried out through surveys based on the Servqual model where it was established that reality is exceeded by expectations, reflecting the poor quality of service. Therefore, based on this, an improvement proposal was designed where the strategic approach (mission, vision, values) was established, the strategic formulation with the aim of positioning itself as a leader in market satisfaction and five strategies that led to the design of the programming where four strategic axes were structured as programs that include thirty-one projects as well as their respective indicators and managers.